Web application to report the monthly attendance of the personnel working in the educational institutions at UGEL Abancay - Contreras Meza, Danyra (2020)
The main objective of this thesis research was to improve the preparation of the monthly assistance report of the staff working in the Educational Institutions of the UGEL Abancay, as well as to reduce the time spent and the costs generated to issue the final consolidated of the monthly assistance reports to the Remuneration Area. The problem that existed in the Personnel Office was that the processes were not automated, so there was no exact control of those Educational Institutions that sent their monthly attendance report, it is more in many cases the information contained in the report It was complete, for example when the director reported a delay, the report did not specify the minutes of that delay, after this situation each report should be extensively verified. The research was applied type, explanatory level and quasi-experimental design, based on the agile SCRUM software development methodology. Finally, when using the SYSCO web application, the preparation of the monthly assistance report will be significantly improved, reducing the time it took to issue the final consolidation by 97%, the costs that were generated in the consolidation were also reduced by 83.85% of the monthly assistance reports in the Personnel Office, this concludes with the implementation of the SYSCO web application, satisfactory results were obtained